The spatial frequency of climatic conditions affects niche composition and functional diversity of species assemblages: the case of Angiosperms - Fournier, Bertrand; Vázquez‐Rivera, Héctor; Clappe, Sylvie; Donelle, Louis; Braga, Pedro Henrique Pereira; Peres‐Neto, Pedro R.; Violle, Cyrille (Ecology letters, 2020)
Climatic conditions vary in spatial frequency globally. Spatially rare climatic conditions provide fewer suitable environments than common ones and should impose constraints on the types of species present locally and regionally. We used data on 467 North American angiosperms to test the effects of the spatial frequency of climatic conditions on ecological niche specialisation and functional diversity. We predicted that rare climates should favour generalist species that are able to inhabit a broader range of climatic conditions. Our results show that climate frequency filters species that differ in niche breadths and rare environments host species combinations with greater functional diversity. The proposed analytical approaches and hypotheses can be adapted to investigate different aspects of ecological assemblies and their biodiversity. We discuss different mechanisms regarding how spatial frequency of environments can affect niche composition and functional diversity. These should be useful while developing theoretical frameworks for generating a deeper understanding of its underpinnings. Climatic conditions vary in spatial frequency globally. Spatially rare climatic conditions provide fewer suitable environments than common ones and should thus impose constraints on the types of species that are present in local communities and regional pools. Our results provide evidence that climate frequency and local climate heterogeneity filter species that differ in their niche breadths and that rare environments host combinations of species with greater functional diversity.